Characterisation of solid flux in packed-fluidized bed: Mixing response of a pulse input during fluidization - Bengtsson, Mårten (My University, 2022)
Fluidized beds have been around for more than 100 years and new applications are constantly developed. One of them, chemical looping combustion technique(CLC), works by letting the fuel react with fluidized solid oxygen carrier instead of air. Previous work have shown that CLC can produce combustion conditions with pure CO2 flue gas stream [1], which would be more cost effective to pressurize and store compared to flue gas stream from air-combustion. One of the drawbacks of CLC is poor gas-mass transfer and the fluidized bed inability to achieve counter-current flow[1]. One approach that has shown improvement on the mass transfer is to introduce packing material to the fluidized bed to facilitate counter-current flow. Earlier work has shown packing material in the fluidized bed greatly increased the conversion of fuel to CO2 in CLC applications. This study investigated the potential of generating counter-current flow patterns for packed-fluidized bed, which can allow for reactor designs with better performance than thermodynamic equilibrium. To investigate the mixing response, a laboratoryscale cylindrical tubular reactor with dimensions 1 m high and 12 cm in diameter was used. Olivin sand with a diameter of 250-300 μm was used as bed material. The bed was fluidized with no packing material as a reference and the experiment were done with ASB 25.4 mm and ASB 6.35 mm as packing materials, at a 2-2.5:1 ratio packing to bed height, with a bed height of 20 cm. A magnetic tracer, magnetite of size 180-212 μm, together with magnetic sensors placed 13(outlet) and 47(inlet) cm from the the distributor plate were used to investigate the degree of plug flow using a pulse input method. Pressure drop over the reactor was measured with 4 sensors, 13.2, 7.6 and 2.1 cm from the bottom. One was placed in the windbox before the distribution plate as reference. The bed was fluidized at superficial gas velocity of 0.1 and 0.3 m/s. Experiments were repeated three times per setup expect for when superficial gas velocity was 0.1 m/s and there was no packing in the bed. This due to insufficient fluidization. Introducing packing material ASB 2.54 mm increased the degree of plug flow for both velocities, high velocity of 0.3 m/s showed higher degree of plug flow compared to 0.1 for the packing material ASB 25.4 mm. ASB 6.35 mm was too small and blocked the outlet yielding no plug flow or meaningful results. Using packed-fluidized bed increase the potential for plug flow and potential for efficient counter-current flow for fluidized bed. More work has to be done to further investigate the effect of confined beds on counter-current flow patterns.
Keywords: packed-fluidized bed; tracer; pulse input; fluidized bed